President's Message - McLeod, Bonnie (Operating Room Nurses Association of Canada Journal, 2010)
At the recent Surgical Safety Saves Lives Workshop in Vancouver, I had the privilege of representing perioperative nurses on an interdisciplinary panel. The participants included a Chief Executive Officer of an eastern hospital, two surgeons, an anesthesiologist, and a member of ‘Patients for Patient Safety’. The discussion was structured by questions delivered by a facilitator: “(1) Why do you think the checklist has received so much attention; (2) Why might surgeons/anesthesiologists/nurses be opposed to using the checklist; and (3) How has using the checklist influenced or changed the way you practice?”